Observability of Boolean networks via matrix equations. (January 2020) - Yu, Yongyuan; Meng, Min; Feng, Jun-e
Abstract: From the new perspective of logical matrix equations, observability of Boolean networks (BNs) is investigated in this paper. First, it is shown that one BN is locally observable on the set of reachable states if and only if the constructed matrix equations have a unique canonical solution. Then, combining with an equivalence relation, a novel condition is established to verify global observability. Finally, an example is worked out to illustrate the obtained results.